Development of Community-Based Tourism Management Post Pandemi Covid-19 at The Pinussari Wanawisata Object, RPH Mangunan, KPH Yogyakarta - Masruri, Niskan Walid; Fermansyah, Deki; Metananda, Arya Arismaya; Suhada, Nur; Daulay, Muhammad Haidar (Journal of Tropical Upland Resources (J. Trop. Upland Res.), 2023)
Abstract. The community-based ecotourism management program is a form of realization of a social forestry scheme that involves the full participation and role of the community in forest management. Since the end of 2019 there has been a pandemic which has had a major impact on all sectors, one of which is the natural tourism sector. This research aims to formulate a strategy for developing ecotourism management as an effort to recover from the Covid-19 pandemic. The research was conducted at Wanawisata Pinussari using data collection techniques in the form of in-depth interviews, field observations, and literature studies. Data analysis was carried out using a combined method through triangulation and SWOT techniques. The results of the study show that: (1) tourism management is divided into three management aspects involving the active participation of members, namely institutional management, area management and tourism business management; (2) The strategy for developing ecotourism management after the Covid-19 pandemic is to provide motivation and increase community participation in managing Pinussari Ecotourism, foster craft-making skills, create outdoor facilities for children, increase member knowledge regarding plant footprint recognition so that skills in managing forests can be improved, as well as increasing the mindset in studying the development of natural tourism trends in the new normal era. Keywords: ecotourism, community empowerment, Pinussari